On the diversity of intelligence - Lidin, Konstantin; Golovnya, Svetlana (project baikal, 2025)
Intelligence as one of the ways of understanding the world can manifest itself in a wide range of diverse forms. Nevertheless, there is a steady tendency to reduce various forms of intelligence to a certain generalized, average value. Using the example of two periods of accelerated scientific and technological development (the sixties and eighties of the nineteenth and twentieth centuries), it is shown that the predominance of the trend towards uniformity gives progress an inhumane and pathogenic character. On the contrary, encouraging diversity in the manifestations of intelligence accelerates innovation and gives them more humane forms.